Vaginal Bleeding in an Infant with Extreme Prematurity - Wing Yiu Sarah Poon; Joanna Yuet Ling Tung (Case Reports in Pediatrics)
Background. Minipuberty of infancy refers to the transient activation of the hypothalamic-pituitary-gonadal (HPG) axis during the first few months of life. Studies have documented a more exaggerated and prolonged gonadotropin surge in preterm infants compared with term infants. We present a case of minipuberty presenting with vaginal bleeding at the corrected age of 3 months of life. Case Presentation. A former 23 + 6-week infant presented with intermittent vaginal bleeding in the diaper at the corrected age of 3 months. Physical exam showed bilateral breast buds of 0.5 cm–1 cm with no signs of pubarche. Investigations showed pubertal levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and estradiol. As she was impressed to have exaggerated minipuberty due to extreme prematurity, no intervention was given. Repeated hormonal workup at the corrected age of 8 months showed decreasing trend of gonadotropin and estradiol levels. Vaginal bleeding resolved, and breast buds also regressed clinically. Conclusion. Our case illustrated that the robust surge of gonadotropin in an ex-premature infant can in fact result in endometrial maturation and present as vaginal bleeding. Though the mechanism of this alteration in the HPG axis in prematurity is not clearly understood, pediatricians should be aware of the benign and self-limiting nature of this phenomenon and avoid unnecessary intervention.